Four-inch high quality crack-free AlN layer grown on a high-temperature annealed AlN template by MOCVD. (December 2021) - Liu, Shangfeng; Yuan, Ye; Sheng, Shanshan; Wang, Tao; Zhang, Jin; Huang, Lijie; Zhang, Xiaohu; Kang, Junjie; Luo, Wei; Li, Yongde; Wang, Houjin; Wang, Weiyun; et al.
Abstract: In this work, based on physical vapor deposition and high-temperature annealing (HTA), the 4-inch crack-free high-quality AlN template is initialized. Benefiting from the crystal recrystallization during the HTA process, the FWHMs of X-ray rocking curves for (002) and (102) planes are encouragingly decreased to 62 and 282 arcsec, respectively. On such an AlN template, an ultra-thin AlN with a thickness of ~700 nm grown by MOCVD shows good quality, thus avoiding the epitaxial lateral overgrowth (ELOG) process in which 3–4 μ m AlN is essential to obtain the flat surface and high crystalline quality. The 4-inch scaled wafer provides an avenue to match UVC-LED with the fabrication process of traditional GaN-based blue LED, therefore significantly improving yields and decreasing cost.